Pilot scale thermal and alternative pasteurization of tomato and watermelon juice: An energy comparison and life cycle assessment. (10th January 2017) - Aganovic, Kemal; Smetana, Sergiy; Grauwet, Tara; Toepfl, Stefan; Mathys, Alexander; Van Loey, Ann; Heinz, Volker
Abstract: The energy balance and life cycle assessment (LCA) of conventional (thermal) and alternative (pulsed electric fields (PEF) and high pressure processing (HPP)) technologies for preservation of tomato and watermelon juice have been evaluated. A comparison between technologies was performed at an equivalent level of microbial inactivation whilst considering the same production capacity on a pilot scale using industrial scale equipment. The data included in the study, such as selected processing conditions, energy consumption, water use, cleaning agents and maintenance, were experimentally collected. For the LCA two main systems were identified: (1) the first system reviewed only the processing stage of juice production (from "gate to gate"), and (2) the second included the expansion of the boundaries to the agricultural production stage and waste treatment during juice preparation and processing (from "farm to gate"). Comparable energy uptake was observed when the same technology for two different juices was compared. In terms of energy consumption, the highest specific energy uptake was recorded for HPP, resulting in an energy consumption of 0.20 kWh/l of juice. Slightly less energy was required by PEF processing with 0.12 kWh/l, followed by thermal with 0.04 kWh/l of juice. As to the environmental impact, expected differences were observed between the technologies based on the differences in energy consumption. Even though the differences of processing stage were assigned to the use of energy, the largest environmental impact was associated with the 250 ml PET bottles production (∼85%). Considerable differences were outlined between the two juices for the "farm to gate" analysis, where tomato juice had a higher impact compared to watermelon juice. From the sensitivity analysis, different strategies for diminishing the impact were identified. They are associated with raw material production (field tomatoes), waste amount decreasing (type of watermelons selection) and relevant packaging selection (HDPE vs. PET). Highlights: Comparison based on microbial equivalence and same production capacity. Highest energy uptake recorded for HPP, followed by PEF and thermal. Environmental impact differences related to energy consumption of each technology. Largest environmental impact is associated with 250 ml PET bottles production.